MODERN APPROACH TO THE RETINOPATHY OF PREMATURITY TREATMENT - Radovanović, Drakče (Medicinski časopis, 2018)
Retinopathy of prematurity is a proliferative retinopathy that occurs in prematurely born children. It is still the leading cause of preventable childhood blindness worldwide. The aim of this paper is to present the therapeutic modalities for the рetinopathy of prematurity. Current gold standard treatment is the laser photocoagulation of avascular retina in order to reduce its existing hypoxia. Expanding our knowledge of the pathogenesis of рetinopathy of prematurity, and the knowledge of the laser therapy efficiency and complications as well, new therapeutic options appear (intravitreal application of anti VEGF, gene therapy and administration of supplements). In order to avoid the visual function loss in prematures caused by retinopathy of prematurity, screening of the premature newborn is the first choice. Key words: retinopathy of prematurity, anti VEGF, childhood blindness